Disparities in 17-Hydroxyprogesterone Caproate Offer and Uptake in Pregnancies at a Risk of Preterm Birth - Berhie, Saba H.; Riley, Laura E.; Bryant, Allison S. (American Journal of Perinatology, 2019)
Objective To evaluate the offer, acceptance, uptake, and patient experience with 17-hydroxyprogesterone caproate (17OHP-C) over the course of 10 years.Study Design This is a retrospective cohort study with a qualitative component. We identified all women with spontaneous preterm deliveries with subsequent births in our hospital between 2005 and 2015. We used linear regression to calculate unadjusted odds ratios for 17OHP-C offer, acceptance, and doses received associated with predictors of interest, and multivariable modeling further adjusted for potential confounders. A grounded theory approach was used to glean recurrent themes surrounding the patient experience.Results A total of 265 women fit the eligibility criteria; 39.6% were offered 17OHP-C and 83.8% accepted 17OHP-C. The mean number of documented 17OHP-C doses was 15.7 ± 5.4. Women were less likely to be offered 17OHP-C if they had public insurance or if their earliest preterm birth was of greater gestational age. Non-Hispanic black women were documented to have received four fewer doses than white women. We also identified recurrent themes that hindered acceptance and adherence to 17OHP-C: insurance difficulties, unstable housing, lack of childcare, and job inflexibility.Conclusion Women at a risk of preterm birth are more likely to be offered and receive 17OHP-C if they have private insurance and have had an earlier preterm birth. Non-Hispanic black women were documented to have received fewer doses of 17OHP-C than white women. Further inquiry into the structural causes that lead to disparities in care for women at a risk for preterm birth is important.
Keywords: preterm birth; intramuscular hydroxyprogesterone; health disparities; qualitative assessment